Global Value Chains of Export in the Andean Community 2000-2015 - Tello, Mario D. (2026)
This study estimates eight standard indicators of Global Value Chains (GVCs) in the four member countries of the Andean Community (CAN) for the years 2000, 2005, 2010, and 2015. The evidence suggests that most GVCs in the region are of the simple type, as a significant portion of exportable goods is used as intermediate inputs in trade among partner countries within the region. Consequently, the CAN's participation in complex GVCs –those in which export products cross borders at least twice– remains limited. Exploring the development of complex GVCs represents a key opportunity to diversify the export capacity of the Andean Community.